Evaluation of Ubtan – A traditional indian skin care formulation. (4th November 2016) - Biswas, Rajarshi; Mukherjee, Pulok K.; Kar, Amit; Bahadur, Shiv; Harwansh, Ranjit K.; Biswas, Sayan; Al-Dhabi, Naif Abdullah; Duraipandiyan, V.
Abstract: Ethnopharmacological relevance: 'Ubtan' is a traditional herbal formulation in the Indian system of medicine being used in India and its subcontinent for a long time. Several commercial skin care formulations are marketed throughout this region as the name of Ubtan. Therefore, it is worthwhile to evaluate Ubtan in respect of its efficacy as skin care formulation. Aim of the study: The present study was designed for the preparation of Ubtan and standardization through the chromatographic techniques by using suitable phyto-markers. Further, its antioxidant, sun protection factor (SPF) and anti-tyrosinase potential have been explored. Materials and methods: Four in-house formulations (UF-1, UF-2, UF-3 and UF-4) were prepared by mixing a varied quantity of each powdered plants, i.e. turmeric ( Curcuma longa L.), Chickpea ( Cicer arietinum L.) and sandalwood ( Santalum album L.). Optimization of the formulations was made by evaluating its biological activity through in vitro assay. Evaluation of physicochemical properties of the optimized formulation (UF-1) has been carried out by analysis of pH, flow properties and stability. Moreover, RP-HPLC (reverse phase - high performance liquid chromatography) and HPTLC (high performance thin layer chromatography) standardization of UF-1 was performed for its quantitative and qualitative analysis. Results: Ubtan formulations (UF-1to UF-4) showed free radical scavenging and ferric reducing potential. It may be due to its high phenolic and flavonoid content. Statistically, significant Pearson's correlation (r) was confirmed the positive correlation between phenolic content and SPF of the formulations. The tyrosinase inhibition study indicated that the formulations showed both diphenolase and monophenolase inhibitory activity. Among four formulations, UF-1 showed notable biological activity ( p <0.05). The content of curcumin and ascorbic acid was found to be 1.6% and 2.1% w/w respectively in UF-1 through RP-HPLC estimation. Physiochemical properties of the UF-1 exhibited good flow rate and aqueous solubility. From the stability studies, it can be anti cipated that the UF-1 was stable at 40 °C for longer periods. Microbial load count and heavy metal content (lead-Pb, arsenic-As, mercury-Hg and cadmium-Cd) of the formulation was also within the permissible limit of a pharmacopeial standard. Conclusion: This scientific exploration helps to set the quality and safety standard of traditional cosmetic formulation, Ubtan and its further use as an herbal skin care product. Graphical abstract: